Bargaining without boundaries : the multinational corporation and international labor relations - Flanagan, Robert J.; Weber, Arnold R.; University of Chicago; McKinsey Foundation for Management Research (New York, N.Y.); Johnson Foundation (Racine, Wis.) (Chicago : University of Chicago Press, 1974)
This volume is a report of the proceedings of a seminar on the industrial relations issues raised by multinational corporations. The focus of the seminar was on the actual impact of multinational corporations on industrial relations systems and the actual and prospective responses of industrial relations institutions to these consequences. Considerable attention was also devoted to an analysis of the alternative policies that might be adopted by unions, management, or government.
"Proceedings of a conference sponsored by the Graduate School of Business, University of Chicago, the McKinsey Foundation, and the Johnson Foundation."
Includes bibliographical references and index.
rpm 27/02/2018
loans
Keywords: Industrial relations; International business enterprises; Collective bargaining